2006
DOI: 10.1203/01.pdr.0000220335.05588.ea
|View full text |Cite
|
Sign up to set email alerts
|

Human Congenital Infection With Trypanosoma cruzi Induces Phenotypic and Functional Modifications of Cord Blood NK Cells

Abstract: ABSTRACT:We studied the phenotype and activity of cord blood natural killer (NK) cells in newborns congenitally infected with Trypanosoma cruzi. We found that the proportion of CD56 bright NK cells was significantly decreased in cord blood from these newborns, suggesting they may have been recruited to secondary lymphoid organs. The remaining CD56bright NK cells exhibited a defective ability in the production of interferon (IFN)-␥ following in vitro activation with interleukin (IL)-12 ϩ IL-2 or IL-12 ϩ IL-15 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…They are also numerous in the decidua during gestation [5,14] . The proportions of circulating CD56 bright and CD56 dim subsets are rather stable over time between birth and adult life, though CD56 bright NK cell numbers were reported, by some authors including our group, to be slightly higher in newborns [12,15,16] .…”
Section: Characterization Of Nk Cells In Early Lifementioning
confidence: 48%
See 1 more Smart Citation
“…They are also numerous in the decidua during gestation [5,14] . The proportions of circulating CD56 bright and CD56 dim subsets are rather stable over time between birth and adult life, though CD56 bright NK cell numbers were reported, by some authors including our group, to be slightly higher in newborns [12,15,16] .…”
Section: Characterization Of Nk Cells In Early Lifementioning
confidence: 48%
“…We previously described for the first time that fetuses were able to develop mature CD8 + T-lymphocyte responses in response to congenital infection with Trypanosoma cruzi, the protozoa agent of Chagas disease in South America [66] , indicating that neonatal immune defects are not absolute. To investigate the mechanisms underlying the capacity of this intracellular pathogen to overcome fetal immune immaturity, we have studied the phenotype and activity of CB NK cells in such newborns [16] . We found that they displayed a reduced proportion of circulating CD56 bright NK cells, suggesting NK cells may have been recruited to secondary lymphoid organs.…”
Section: Protozoal Infectionsmentioning
confidence: 99%
“…The acquisition of CD85j surface expression on CD3 + T cells was more variable but the proportion of positive T cells was significantly increased compared with uninfected newborns (P < 0Á05). It is of interest to note that such iNKR induction on neonatal CD8 + T cells up-regulation was not detected on NK cells, 23 providing evidence that the induction of iNKRs on T cells was not a consequence of T. cruzi infection that would up-regulate iNKRs on all lymphocyte populations. Importantly, the expression of not only KIRs but also of CD94/NKG2A was strictly associated with the infection of the baby because uninfected newborn infants of T. cruzi-infected mothers lacked iNKR expression on their T cells (data not shown).…”
Section: Kir Expression On Cord Blood T Cells Is Induced Upon Congenimentioning
confidence: 99%
“…In addition, an increase in TNF-α receptors is also observed, when compared to infected newborns or healthy newborns with healthy mothers (Hermann, et al 2004;Carlier, 2005;Hermann, et al 2006). Therefore, non-infected newborns with Chagasic mothers are able to mount a T CD8+ cellular immune response similar to that of an adult (Hermann, et al 2002).…”
Section: Figure 1: Placental Maternofetal Barriermentioning
confidence: 99%
“…Similarly, transmitting mothers have a higher parasite load associated with higher parasitemia, diminished capacity to produce IFN-γ by mononuclear blood cells, inability to produce IL-2 as a specific response to the parasite (Hermann, et al 2004;Carlier, 2005;, a greater capacity to produce IL-10 (anti-inflammatory cytokine) , and low levels of circulating TNF (Garcia, et al 2008). On the contrary, non-transmitting Chagasic mothers show high monocyte activation levels (Carlier, 2005;Hermann, et al 2006) and high levels of circulating TNF (Garcia, et al 2008).…”
Section: Figure 1: Placental Maternofetal Barriermentioning
confidence: 99%